Fairy Tale Films - Matrix Sidney E. (Utah State University, University Libraries, 2010)
In this, the first collection of essays to address the development of fairy tale film as a genre, Pauline Greenhill and Sidney Eve Matrix stress, ""the mirror of fairy-tale film reflects not so much what its audience members actually are but how they see themselves and their potential to develop (or, likewise, to regress)."" As Jack Zipes says further in the foreword,